Comparative analysis between machine learning algorithms in efficiency of Coronary Heart Disease (CHD) prediction - Oishi, Fayza Rezwana; Al Mahadi, Mehnaj; Parvez, Omar Bin (Brac University, 2020)
Cataloged from PDF version of thesis.